Asuhan Kebidanan Komprehensif Balita 36 Bulan dengan Berat Badan Kurang - Ramdhani, Riva; Lestari, Dian; Amanda, Atika; Nursanti, Rina (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2025)
The toddler period (golden period) is a golden period that is very sensitive to the environment and this period lasts very short and cannot be repeated. This study aims to analyze comprehensive midwifery care in a case of underweight in An. A 36 months using an intervention of consumtion papaya 100 gr per a day at PMB Lismarini, South Sumatera. The study employed a case study method with a descriptive qualitative approach. Data were collected through interviews, SOAP (Subjective, Objective, Assessment, Plan) assessment, observation, and documentation. Interventions included consumtion papaya, improved personal hygiene, recommendations for a nutritious diet, and psychological support. The results indicated Obstetric diagnosis is carried out based on the results of the assessment and interventions that have been carried out comprehensively. It is recommended that education on cases of underweight in toddlers can be studied with more focused data related to client health in improving toddler health for readiness to become a healthy and strong next generation.